Prevalence and type distribution of human papillomavirus in squamous cell carcinoma and intraepithelial neoplasia of the vulva. Issue 6 (21st June 2017) - Faber, Mette T.; Sand, Freja L.; Albieri, Vanna; Norrild, Bodil; Kjær, Susanne K.; Verdoodt, Freija
Abstract : In this updated systematic review and meta‐analysis, we estimate the pooled prevalence of human papillomavirus (HPV) DNA and HPV type distribution in squamous cell carcinoma of the vulva (vulvar cancer) and vulvar intraepithelial neoplasia (VIN). PubMed, Embase and Cochrane Library databases were used to identify studies published between 1990 and 2015 and using a PCR‐based or hybrid capture test to evaluate the presence of HPV DNA in vulvar cancer or VIN. Pooled estimates of the HPV prevalence with corresponding 95% confidence intervals (CI) were calculated based on a random effects model. The I 2 statistic was used to describe the amount of heterogeneity. In meta‐regression analyses, potential sources of heterogeneity were evaluated. We identified 92 eligible papers, comprising altogether 5, 015 cases of vulvar cancer (64 papers) and 2, 764 cases of VIN (48 papers). The pooled prevalence of HPV in vulvar cancer was 39.7% (95% CI: 35.1–44.4%). Overall, 76.3% (95% CI: 70.1–82.1%) of VIN lesions tested HPV‐positive, while the HPV prevalence in new subcategories of VIN, uVIN and dVIN, was 86.2% (95% CI: 73.5–95.5%) and 2.0% (95% CI: 0–10.0%), respectively. Substantial between‐study heterogeneity was observed (vulvar cancer: I 2 = 88.4%; VIN: I 2 = 90.7%) with the largest variation between geographical regions. Among HPV‐positive cases, the predominant high‐risk HPV type was HPV16, followed by HPV33 and HPV18. HPV6 was detected as a single infection in a small subset of VIN and vulvar cancer samples. Thus, HPV vaccination targeting these HPV types may prevent a substantial number of vulvar lesions. Abstract : What's new? Over the past few decades, the incidence of vulvar cancer and vulvar intraepithelial neoplasia (VIN) have been reported to increase, particularly among younger women where lesions are more likely to be human papillomavirus (HPV)‐related. In this updated meta‐analysis, the authors found that 40% of vulvar cancers and 76% of VIN lesions were HPV‐related. They evaluated a new classification system for VIN based on HPV involvement and estimated that 86% of uVIN lesions were HPV‐related. HPV16, 33, and 18 were the predominant types. Thus, HPV vaccination targeting these HPV types may prevent a substantial number of vulvar lesions.